ESTABLISHMENT OF THE BRACHIARIA RUZIZIENSIS X BRACHIARIA BRIZANTHA HYBRID UNDER HUMID TROPICAL CONDITIONS - Ara G., Miguel (2007)
The hybrid Brachiaria ruziziensis x Brachiaria brizantha (pasto Mulato) has been released as a highly productive tropical forage. This new option is being tested at Pucallpa in a field trial under a combination of NP fertilizer rates (0, 75 y 150 kg/ha/year of N and 0, 25 y 50 kg/ha/year of P). Establishment evaluations, resulting from measuring seedling emergence and biomass cover at 3, 6, 9, and 12 weeks after planting, showed Mulato as a forage with an excellent establishment potential, particularly with high seedling emergence and coverage rate, and apparently tolerant to N deficiency, as compared with Brachiaria brizantha.